Foundations of the rule-based system ρLog - Marin, Mircea; Kutsia, Temur (Journal of applied non-classical logics, 2006)
We describe the foundations of a system for rule-based programming which integrates two powerful mechanisms: (1) matching with context variables, sequence variables, and regular constraints for their matching values; and (2) strategic programming with labeled rules. The system is called ρLog, and is built on top of the pattern matching and rule-based programming capabilities of Mathematica.